ANALISIS PEMIKIRAN IBNU FARIS MENGENAI ILMU LUGHAH DALAM KITAB ASH-SHAHIBIY - Amalia, Henni (At-Tafkir, 2017)
Ilmu lughah is all about knowledge and discussions in arabiclanguage. Some Arab linguist also different on the object of thestudy in accordance with the used name, Ibnu Faris is one ofArab linguists who interpreted in his book of ash-Shahiby thatfiqhul lughah is science all about the Arabic pronunciation, andIlmu Lughah is a taufiq or ilham that from Allah. The purpose ofthis study to inform the argument of Ibnu Faris about ilmu lughahprincipal based on theorem reinforce his argument. Thisresearch is used descriptive qualitative method. The results ofthis study; (1) to indicate the principle of language learning ofknowing the common nouns in daily life; (2) ilmu lughah is ataufiq that come from Allah through intelligent of the humanbeing.